Pancreaticopleural fistula causing amylase-rich pleural effusion: Case series from a rural tertiary care hospital - Rashni Belandor Janardhanachar; Veena Bhaskar S. Gowda; Sapna Purushotham; Aishwarya S. Durgad (Lung India)
Pancreaticopleural fistula (PPF) is a rare (<1%) complication of acute and/or chronic pancreatitis which causes recurrent massive pleural effusions. Patient presents with respiratory symptoms rather than abdominal symptoms, which makes the diagnosis challenging and delayed. Amylase-rich pleural effusions have been reported in pancreatic diseases, oesophageal rupture, and malignant pleural effusions. Pancreatitis-related effusion including PPF should be kept in mind when a patient with chronic alcohol consumption presents with an effusion and PF amylase may aid with diagnosis. We present a case series of four young males with a history of recurrent massive pleural effusions and their varied clinical presentations, diagnostic work-up, approach and management in a rural tertiary care hospital in south India, thus contributing to literature as well emphasizing the importance of such easily available biomarkers in day-to-day practice.